2022
DOI: 10.1073/pnas.2112518119
|View full text |Cite
|
Sign up to set email alerts
|

A dialogue-like cell communication mechanism is conserved in filamentous ascomycete fungi and mediates interspecies interactions

Abstract: Significance This study reveals that a dialogue-like communication mechanism, which mediates cell–cell fusion in filamentous fungi, is a conserved complex trait. It allows the communication and behavioral coordination of cells of distantly related species and mediates their mutual attraction and subsequent physical contact, although interspecies fusion does not occur. Through the activation of this signaling machinery, one species can reprogram the developmental program of the other fungus. These dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Moreover, genomic evidence for horizontal gene transfer from F. oxysporum to V. dahliae has been reported (Chen et al, 2018). We speculate that under particular selective conditions the two species might be able to undergo vegetative fusion or communicate via physical cell contact (Haj Hammadeh et al, 2022), and that their pheromone-sensing systems might mediate such interspecific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genomic evidence for horizontal gene transfer from F. oxysporum to V. dahliae has been reported (Chen et al, 2018). We speculate that under particular selective conditions the two species might be able to undergo vegetative fusion or communicate via physical cell contact (Haj Hammadeh et al, 2022), and that their pheromone-sensing systems might mediate such interspecific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on experiments with a so deletion strain in N. crassa, it was hypothesized that the corresponding protein is crucial for signal secretion [18,20]. As several other studies have indicated, the fusion signal might be conserved amongst fungi and can induce chemotropic interactions in distantly related species such as Botrytis cinerea and N. crassa [25]. The inter-species formation of germling fusion has also been shown to promote genetic variability in several Colletotrichum species [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…As the cell-to-cell dialogue appears to be based on a single, chemical communication channel, it is proposed that the two involved cells undergo oscillatory secretion of a signaling compound with a refractory period that prevents self-stimulation and can contribute to overcoming critical threshold concentrations (1). We recently studied the cell-to-cell dialogue during trap formation in the nematode-trapping fungus Arthrobotrys flagrans (Duddingtonia flagrans) (9). A. flagrans is able to switch from a saprotrophic to a predatory lifestyle, and sophisticated signaling regimes between the fungus and its prey, Caenorhabditis elegans, control trap formation, attraction of the prey and attack of the nematode (11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, signal oscillations have been described at the hyphal tips during the fusion of hyphal cells (5)(6)(7). These signal oscillations were named cell-to-cell dialogue and are probably based on a conserved diffusible signaling molecule, which remains to be discovered (8)(9)(10). As the cell-to-cell dialogue appears to be based on a single, chemical communication channel, it is proposed that the two involved cells undergo oscillatory secretion of a signaling compound with a refractory period that prevents self-stimulation and can contribute to overcoming critical threshold concentrations (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation